Adherence and retention of African Americans in a randomized controlled trial with a yoga-based intervention: the effects of health promoting programs on cardiovascular disease risk study. Issue 6 (17th August 2020) - Okhomina, Victoria I.; Seals, Samantha R.; Anugu, Pramod; Adu-Boateng, Godwin; Sims, Mario; Marshall, Gailen D.
ABSTRACT: Objectives: Sedentary lifestyle is a risk factor for cardiovascular disease (CVD). Few alternative lifestyle interventions, such as yoga practice, focus on African Americans (AA), the population most vulnerable to CVD. Our objective is to compare the retention and adherence rates between yoga, walking, and health education interventions while providing information about the acceptance of various yoga regimens. Design: Three hundred seventy-five AA participants were recruited exclusively from an active cohort study and randomized into a 48-week study (24 weeks intervention, 24 weeks follow-up) with 5 health promotion interventions: high frequency yoga, moderate frequency yoga, low frequency yoga, guided walking, and health education. In addition to examining the separate yoga interventions, a pooled yoga intervention is considered for comparison to guided walking and health education. Participant retention, adherence, and vitals were monitored at each intervention session. Participants were also scheduled for four clinic visits throughout the study where blood panels, health behavior, and medication surveys were administered. Results: Of the 375 participants recruited, 31.7% did not complete the study. At baseline, in both the guided walking group and the high frequency yoga group, there were significant differences between those who completed the study and those who did not. Although intervention retention in the pooled yoga program (78.3%) was higher compared to the walking (60%) and education programs (74.3%) ( p  = 0.007), differences in post-intervention retention was not significant. Median adherence rates for the pooled yoga program exceeded rates for guided walking and education with moderate frequency yoga out performing high and low frequency yoga. Conclusion: Study-defined retention success rates were not reached by all health promotion programs. However, retention and adherence rates for the pooled yoga program show that older African Americans are receptive to participating in yoga-based health promotion practices.